2007
DOI: 10.1038/ng2074
|View full text |Cite
|
Sign up to set email alerts
|

A gene in the multidrug and toxic compound extrusion (MATE) family confers aluminum tolerance in sorghum

Abstract: Crop yields are significantly reduced by aluminum toxicity on highly acidic soils, which comprise up to 50% of the world's arable land. Candidate aluminum tolerance proteins include organic acid efflux transporters, with the organic acids forming non-toxic complexes with rhizosphere aluminum. In this study, we used positional cloning to identify the gene encoding a member of the multidrug and toxic compound extrusion (MATE) family, an aluminum-activated citrate transporter, as responsible for the major sorghum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
645
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 668 publications
(676 citation statements)
references
References 27 publications
15
645
2
3
Order By: Relevance
“…In a genome-wide association study targeting adaptation to low P in sorghum (Leiser et al, 2014b), the most significant association with grain yield was found for an SNP at position 71.1 Mb on chromosome 3 (71178053), only 35.7 kb from the aluminum tolerance gene Sorghum bicolor multidrug and toxic compound extrusion (SbMATE), which underlies the aluminum tolerance locus Aluminum tolerance Sorghum bicolor (Alt SB ; Magalhaes et al, 2007). As SNPs associated with grain yield were also found within Alt SB and SbMATE, this suggests a possible pleiotropic effect of SbMATE in providing tolerance to aluminum toxicity and to low-P conditions (Leiser et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…In a genome-wide association study targeting adaptation to low P in sorghum (Leiser et al, 2014b), the most significant association with grain yield was found for an SNP at position 71.1 Mb on chromosome 3 (71178053), only 35.7 kb from the aluminum tolerance gene Sorghum bicolor multidrug and toxic compound extrusion (SbMATE), which underlies the aluminum tolerance locus Aluminum tolerance Sorghum bicolor (Alt SB ; Magalhaes et al, 2007). As SNPs associated with grain yield were also found within Alt SB and SbMATE, this suggests a possible pleiotropic effect of SbMATE in providing tolerance to aluminum toxicity and to low-P conditions (Leiser et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has been observed in a wide variety of plant species, including both dicots and monocots such as wheat (Triticum aestivum), barley (Hordeum vulgare), Arabidopsis, and Cassia tora (Delhaize et al, 1993;Ma et al, 1997;Hoekenga et al, 2003;Zhao et al, 2003). Genes responsible for the Alinduced secretion of malate in wheat (ALMT1; Sasaki et al, 2004), and citrate in barley (HvAACT1; Furukawa et al, 2007) and sorghum (SbMATE;Magalhaes et al, 2007) have been identified. Recently, progress in identification of other Al-tolerance genes has also been made.…”
Section: Atstar1 Is Required For Al Tolerance In Arabidopsismentioning
confidence: 99%
“…In any case, increased synthesis of LMWOAs is not necessarily indicative of a higher LMWOA exudation since the limiting step is not the plantinternal concentration of LMWOAs (synthesis) but their rate of release (Delhaize et al 2001). This release is mediated by specific efflux transporters, and their level of activity was shown to be directly linked to malate or citratemediated tolerance to excess aluminum (Delhaize et al 2004;Magalhaes et al 2007). However, putative efflux transporters were not among the root-specific genes differentially expressed between genotypes, corroborating earlier results that neither genotype exuded citrate or malate at high enough concentrations to have a significant effect on P solubilization (Wissuwa 2005).…”
Section: Stress Responsementioning
confidence: 99%